MONITORING DASHBOARD USING LINEAR REGRESSION FOR EMPLOYEE PERFORMANCE - Mochammad Ilham Aziz; Saifulloh Azhar; Satria Pradana Rizki Yulianto; Widodo; Devi Ratnasari; Fatika La Viola Ifanka; Melvien Zainul Asyiqien; Muhammad Oktoda Noorrohman (RADJA PUBLIKA, 2025)
Company management needs to continuously monitor and measure the performance of its employees to ensure the achievement of the goals that have been set. The performance monitoring process requires data and information obtained from 35 employees. The problem is in the process of the employee payroll system, attendance, leave and the main thing is data management for monitoring employees still use conventional method by manual. The results of performance monitoring will then be conveyed to interested parties, efficiently and effectively. After that, the existing data were analyzed using SPSS which stands for Statistical Product and Service Solution. Validity testing can also be done using SPSS and produces a validity test of the data, which is < 0.05 so it is valid. The reliability test of the data is > 0.70, 0.751 for employee salaries and 0.757 for employee performance so it is reliable. The normality test of the data are > 0.05, 0.077 for employee salaries and 0.059 for employee performance so that the data is normally distributed. The linearity test of the data is 0.604 > 0.05, it can be concluded that there is a linear relationship between salary and employee performance. Regression analysis test simple linear data from the data, namely the significance level of 0.001 < 0.05 then the regression model can be used to predict the participation variable or in other words there is an effect of the salary variable on the performance variable.